Use of CFD for optimization of hydraulic structures and hydropower plants - Nowak, Petr; Bílková, Eva (Modeling, Control and Information Technologies: Proceedings of International scientific and practical conference, 2025)
This article deals with new possibilities of using mathematical modelling for optimization in the field of hydraulic engineering elements. Optimization allows to increase the performance of structures while reducing investment costs. An interesting area is the shape optimization of hydropower plant structural elements. Demonstrations of the use of CFD will also cover the area of design of custom hydro turbines.